2012
DOI: 10.1007/s00330-012-2703-z
|View full text |Cite
|
Sign up to set email alerts
|

An initial randomised study assessing free-breathing CCTA using 320-detector CT

Abstract: • Cardiac CT is becoming widely used and some patients are inevitably breathless. • Multidetector CT (e.g. 320) offers new opportunities for the breathless patient. • Free breathing images yielded similar image quality to those obtained using breath-holding. • However, a possibility of higher radiation dose precludes its routine application.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Including those patients could increase the number of unevaluable CCTAs and decrease the diagnostic accuracy in clinical practice. With fast acquisition, such as a temporal resolution of about 40 ms, CCTA images could become free of motion artefacts, even during free breathing [27], but coronary calcifications may still remain a considerable obstacle in some patients. Most studies of this meta-analysis applied spiral CT with retrospective gating.…”
Section: Discussionmentioning
confidence: 98%
“…Including those patients could increase the number of unevaluable CCTAs and decrease the diagnostic accuracy in clinical practice. With fast acquisition, such as a temporal resolution of about 40 ms, CCTA images could become free of motion artefacts, even during free breathing [27], but coronary calcifications may still remain a considerable obstacle in some patients. Most studies of this meta-analysis applied spiral CT with retrospective gating.…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, with the 16-cm wide-detector collimation, CCTA in free-breathing is feasible and demonstrates excellent image quality. 12,20 This scan mode change not only requires more precise timing for the peak enhancement, but also enables shorter enhancement plateau thus shorter injection duration. There have been several previous studies that investigated the feasibility of contrast medium volume reduction in CCTA using the 320-row wide-detector system, 11,21,22 and demonstrated the ability of achieving similar image quality at reduced contrast dosage.…”
Section: Discussionmentioning
confidence: 99%
“…Previous literatures [ 14 , 15 ] reported free-breathing CCTA by dual-source CT, and the heart rate was controlled under 60 bpm. Other scholars [ 16 , 17 ] performed CCTA under free-breathing using 320-MDCT, and the heart rate was required to be 75 bpm or less due to the limitation of temporal resolution. It is thereby shown that free-breathing CCTA can be performed for patients with low heart rates, but there is no report about the feasibility for high heart rate (≥70 bpm).…”
Section: Discussionmentioning
confidence: 99%